HBR women at work series collection. - Making real connections (Harvard Business Review Press); Speak up, speak out (Harvard Business Review Press); You, the leader (Harvard Business Review Press) (HBR women at work series., 2022)
Women often face unique challenges in the workplace, from navigating the wage gap and facing unfair biases to coping with interrupting colleagues and worrying about imposter syndrome. How can you rise above it all and forge a clear path to success? The HBR Women at Work Series Collection brings together strategies and advice to help women advance in their careers. This specially priced collection features You, the Leader, which examines how you can stand out as an aspiring female leader while overcoming the obstacles you face as you chart your way to the top; Speak Up, Speak Out, which will help you be heard in conversations large and small and discover ways to raise issues without raising your voice; and Making Real Connections, which will take you beyond transactional networking and superficial small talk to create valuable work relationships built on trust. Featuring detailed discussion guides, this collection will spark important conversations about where we're at and how to move forward. The HBR Women at Work series spotlights the real challenges and opportunities women experience throughout their careers. With interviews from the popular podcast of the same name and related articles, stories, and research, these books provide inspiration and advice for taking on topics at work like inequity, advancement, and building community. Featuring detailed discussion guides, this series will help you spark important conversations about where we're at and how to move forward.